Analysis of Ecocriticism and Feminism of '7 Manusia Harimau' Novel by Motinggo Busye (Proceedings of English Linguistics and Literature, 2022)
The objective of this study was to find out about ecocriticism and feminism in 7 Manusia Harimau Nove. In this study, the researcher used qualitative research and focuses on descriptive analysis data. The data source for this research the researcher used novel. The result of this research showed that Ecocriticism in this research likes describing the setting of the place, traditional transportation (bicycle), describing beautiful screen in Kumayan village, describing one of direction, natural phenomena such as overflowing water, animal ecosystem, interactions between humans and animals, how to live in the jungle Meanwhile, the feminism that the researcher encounters in the novel 7 Manusia Harimau likes Pita Loka's struggles and journeys in learning such as Pita Loka have a stubborn character, dare to fight against stealth, have a strong determination and can face tests such as taking medicine in which Pitaloka is disturbed by creatures such as animals and creatures that transform into Gumara. In addition, Pita Loka also has a strategy in dealing with enemies, Pita Loka wants to teach or share her knowledge.